The world guide to CSR : a country-by-country analysis of corporate sustainability and responsibility - Visser, Wayne; Tolhurst, Nick. (Sheffield : Greenleaf, 2010)
Provides comparable national profiles that describe the evolution and practice of corporate sustainability and responsibility (CSR) for 58 countries and 5 global regions. Each regional and national profile includes key information about the relevant CSR history, country-specific issues, trends, research and leading organisations. Each regional/country profile includes the following subsections: CSR in context, priority issues, trends, legislation and codes, organisations, case studies, educational institutions, references.--From publisher's description.
A. Regional profiles -- I. Africa / Ullrich Klins, Jurie H. Van Hiekerk, Arnold Smit -- II. Asia / Felipe B. Alfonso, Maria Elena B. Herrera, Fracisco L. Roman -- III. Europe / Laura Maanavilja -- IV. Latin America / Estrella Peinado-Vara, Antonio Vives -- V. Middle East / Abbe Le Pelley -- B. Country profiles -- 1. Argentina / María Irigoyen -- 2. Armenia / Nazareth Seferian -- 3. Australia / Leeora D. Black -- 4. Austria / Alice Schmidt -- 5. Azerbaijan / Ahad Kazimov -- 6. Bangladesh / Niaz Alam -- 7. Brazil / Camila Yamahaki, Tarcila Reis Ursini -- 8. Bulgaria / Deyana Marcheva, Nadejda Loumbeva -- 9. Canada / Dermot Hikisch -- 10. China / Sam Yoon-Suk Lee, Joshua Wickerham -- 11. Colombia / Angela Pinilla Urzola -- 12. Côte d'Ivoire / Ulf Richter -- 13. Denmark / Tania Ellis, Jonas Eder-Hansen -- 14. Finland / Arno Kourula -- 15. Germany / Nick Tolhurst, Aron Embaye -- 16. Ghana / Daniel F. Ofori -- 17. Greece / Kiara Konti -- 18. Hungary / Attila Kun -- 19. Iceland / Hanna Thorsteinsdottir -- 20. India / Bimal Arora, Aparna Mahajan -- 21. Indonesia / Yanuar Nugroho ... [et al.] -- 22. Iran / Alireza Omidvar -- 23. Ireland / Tomás Sercovich -- 24. Israel / Ivri Verbin, Dena Freeman -- 25. Japan / Luke Poliszcuk, Motoko Sakashita -- 26. Jordan / Dima Abdelijalil Maaytah -- 27. Kenya / Judy N. Muthuri, Kiarie Mwaura -- 28. Liberia / Marcus S. Wleh -- 29. Malaysia / Roger Haw Boon Hong -- 30. Mauritius / Renginee G. Pillay -- 31. Mexico / Leonardo J. Cárdenas -- 32. The Netherlands / Jennifer Iansen-Rogers -- 33. Nigeria / Kenneth Amaeshi, Chris Ogbechie -- 34. Norway / Inge Aarhus -- 35. Pakistan / Khadeeja Ashaah Balkhi -- 36. Perú / Cristian Loza Adaui -- 37. The Philippines / Francisco L. Roman, Maria Elena B. Herrera -- 38. Poland / Liliana Anam -- 39. Portugal / Maria Lemos -- 40. Romania / Rodica Milena Zaharia, Alin Stancu, Liviu Chelcea -- 41. Russia / Alexey Kostin -- 42. Saudi Arabia / Tareq Emtairah -- 43. Senegal / Oumhany Sy -- 44. Sierra Leone / Nicole Porto -- 45. Singapore / Thomas Thomas -- 46. South Africa / Mervyn E. King, Derick de Jongh, René Carapinha -- 47. South Korea / Angela Joo-Hyun Kang, Sam Yoon-Suk Lee -- 48. Spain / José Manuel Almela Burgos, Germán Granda Revilla, Ricardo Trujillo Fernández -- 49. Sri Lanka / Lalith Gunaratne, Ravi Fernando -- 50. Switzerland / Heiko Spitzeck -- 51. Tanzania / Sarah Lauwo -- 52. Thailand / Alex P. Mavro Jr. -- 53. Turkey / Dixie O'Donnell -- 54. Uganda / Cedric Marvin Nkiko, David Katamba -- 55. United Arab Emirates / Aparna Mahajan -- 56. United Kingdom / David Grayson -- 57. United States of America / Audra Jones -- 58. Venezuela / Perla Puterman Szomstein.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social responsibility of business; Electronic books